Zigbex wireless sensor actuator network (WSAN) home alarming system for fire detection: article / Mohd Rizal Roslan - Roslan, Mohd Rizal (2010)
As home network technologies are improving, sensors collecting environmental information such as temperature, humidity, and illumination in a building or a house are evolving. One of the many available home network technologies is fire detection. Many sensors have been developed for fire detection using closed-circuit television (CCTV) cameras or fiber-optical sensors. This project presents the application of zigbex wireless sensor/actuator network (WSAN) for fire detection home alarming system. The sensor node will sense the level of temperature and sends the data to the base node and actuator node. The results were display on the oscilloscope Graphical User Interface (GUI) whereas the actuator node would activate the alarm. It can be concluded that fire detection can be controlled wirelessly using zigbex WSAN test-bed.